Effects of Fluvastatin and Bezafibrate Combination on Plasma Fibrinogen, t-plasminogen Activator Inhibitor and C Reactive Protein Levels in Coronary Artery Disease Patients with Mixed Hyperlipidaemia (FACT Study) - Cortellaro, M.; Cofrancesco, E.; Boschetti, C.; Cortellaro, F.; Mancini, M.; Mariani, M.; Paoletti, R.; the FACT Study Centers; on behalf of (Thrombosis and Haemostasis, 2000)
We studied the effects of fluvastatin and bezafibrate in monotherapy and in combination on plasma fibrinogen, t-plasminogen activator inhibitor (PAI-1) and C reactive protein (CRP) in patients with coronary artery disease (CAD) and mixed hyperlipidaemiaIn this randomised, double blind, multicentre trial 333 patients with stable angina pectoris or previous myocardial infarction or coronary revascularisation and mixed hyperlipidaemia (LDL-cholesterol 135-250 mg/dl and triglycerides (TG) 180-400 mg/dl) were randomised to fluvastatin 40 mg, bezafibrate 400 mg, fluvastatin 20 mg + bezafibrate 400 mg or fluvastatin 40 mg + bezafibrate 400 mg treatments for 24 weeks.Plasma fibrinogen significantly decreased after treatment with the combinations fluvastatin+bezafibrate (−14 and −16%) and with bezafibrate monotherapy (−9%). No significant reduction was observed after fluvastatin monotherapy (−4%). No significant changes were observed in PAI-1 and CRP plasma levels. Combination therapy significantly decreased both LDL-C and TG, and significantly increased HDL-C.The combined effects on fibrinogen and plasma lipids achieved by fluvastatin and bezafibrate combination treatment might be more useful than the simple reduction of cholesterol in preventing ischaemic cardiovascular disease.
Keywords: Statin; fibrate; fibrinogen; coronary artery disease